(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article examines the importance of taxes in the state economy, and it is based on the fact that reducing tax debt is one of the most urgent issues in the country today. Opinions and opinions of foreign economists on tax debt reduction have been studied. Tax debts of legal entities, including individual entrepreneurs, were analyzed. Specific features of tax debt collection in developed countries have been studied. Also, the dependence of the increase in tax debt in our republic on the income of taxes and other mandatory payments was analyzed, and scientific proposals and practical recommendations were developed based on foreign experience. Based on the above-mentioned circumstances, proposals and recommendations have been formulated to reduce tax debt in our country, including improving the practice of its effective collection.